x>10+7

x>17

Search

Answered @ 19/08/2019 05:56 PM By answersmine

I hope this helps you

x>10+7

x>17

x>10+7

x>17

1) you can buy 6 candy bars because $5.10 / $0.85 =

6.

To check: 6*0.85=5.10

2) you can find the answer by adding 3 to 12. 3+12=15 n=15 and it said n can be greater than or equal so

N(greater than or equal to sign) 15.

To check: 15-3=12

12=12

16-3>12

13>12

7) x-7=12

+7 +7

X=19

To check: 19-7=12

12=12

8) y/8=7

*8 *8

Y= 56

To check: 56/8=7

7=7

9) 10-4x=6x

+4x +4x

10=10x

/10 /10

X=1

To check: 10-4(1)=6(1)

10-4=6

6=6

Hope this helped!

6.

To check: 6*0.85=5.10

2) you can find the answer by adding 3 to 12. 3+12=15 n=15 and it said n can be greater than or equal so

N(greater than or equal to sign) 15.

To check: 15-3=12

12=12

16-3>12

13>12

7) x-7=12

+7 +7

X=19

To check: 19-7=12

12=12

8) y/8=7

*8 *8

Y= 56

To check: 56/8=7

7=7

9) 10-4x=6x

+4x +4x

10=10x

/10 /10

X=1

To check: 10-4(1)=6(1)

10-4=6

6=6

Hope this helped!

**Answer:**

#1 is 6 candy bars

#2 i think it's n≥15

#3 x= 19/7

**Step-by-step explanation:**

QUESTION 1

We want to expand .

We apply the binomial theorem which is given by the formula

.

By comparison,

.

We substitute all these values to obtain,

.

We now simplify to obtain,

.

This gives,

.

Ans:C

QUESTION 2

We want to expand

.

We apply the binomial theorem to obtain,

.

We simplify to get,

.

We simplify further to obtain,

Ans:B

QUESTION 3

We want to find the number of terms in the binomial expansion,

.

In the above expression, .

The number of terms in a binomial expression is .

Therefore there are 21 terms in the binomial expansion.

Ans:C

QUESTION 4

We want to expand

.

We apply the binomial theorem to obtain,

.

We simplify to get,

.

We simplify further to obtain,

Ans: C

QUESTION 5

We want to expand

We apply the binomial theorem to obtain,

.

We simplify to obtain,

.

This finally gives us,

.

Ans:B

QUESTION 6

We want to expand .

We apply the binomial theorem to obtain,

.

We simplify to get,

.

This will give us,

.

Ans:A

QUESTION 7

We want to find the 6th term of .

The nth term is given by the formula,

.

Where

We substitute to obtain,

.

.

Ans:D

QUESTION 8.

We want to find the 6th term of

The nth term is given by the formula,

.

Where

We substitute to obtain,

.

.

Ans:D

QUESTION 9

We want to find the 6th term of .

The nth term is given by the formula,

.

Where

We substitute to obtain,

.

.

Ans: A

We want to find the 7th term of .

The nth term is given by the formula,

.

Where

We substitute to obtain,

.

.

Ans:A

4# Vertical line is x = 3

5# Horizontal line is y = 7

10# Slope of the line = (-7-8)/(-1-(-4))

= -15/3 = -5

11# Slope of the line = (-3 -5)/(2-2) = -8/0 = infinite, ie the line is parallel to y axis

12# Slope of the line = (-9-(-9))/ ( 0 - (-4)) = 0/4 = 0, ie the line is parallel to x axis

15# 8x - 2y = 4

or, x/0.5 - y/0.5 = 1

or, x/0.5 + y/(-0.5) = 1

Therefore x intercept is 0.5 or 1/2 and y intercept is -0.5 or -1/2

16# y = - 4x + 8

or, 4x + y = 8

or, x/0.5 + y/8 = 1

Therefore x intercept is 0.5 or 1/2 and y intercept is 8

Hope it helps.

Thanks you..!!

The coefficient of x is 10.

So the answer is B.10

So the answer is B.10

Your answer is B) 4. 83 X 10^-6

Thank you

(1)

the equation of a line in slope-intercept form is

y = mx + c ( m is the slope and c the y-intercept )

y = - 3x + 4 is in this form with slope m = - 3

• Parallel lines have equal slopes, thus

y = - 3x + c ← is the partial equation

To find c substitute (- 3, - 7 ) into the partial equation

- 7 = 9 + c ⇒ c = - 7 - 9 = - 16

y = - 3x - 16 ← equation of line

(2)

rearrange 4x + 2y = 10 into slope- intercept form

subtract 4x from both sides

2y = - 4x + 10 ( divide all terms by 2 )

y = - 2x + 5 ← in slope- intercept form with m = - 2

y = - 2x + c ← partial equation

to find c substitute (4, 6 ) into the partial equation

6 = - 8 + c ⇒ c = 6 + 8 = 14

y = - 2x + 14 ← equation of line

**Answer: **

The correct answer is d. (40, 60)

**Step-by-step explanation: **

To start using the linear combination method, you need a variable that will cancel out. To get this, we will multiply the second equation by -20 and then add together.

x + y = 100

-1.4x - y = -116

-----------------

-0.4x = -16

**x = 40**

Now that we have the value of x, we plug into one of the original equations to find y.

x + y = 100

40 + y = 100

**y = 60**

The first one is A, the third is D, the fourth is D, the fifth is 4, the sixth is D, the seventh is D, the tenth is D. Sorry I couldn't do all but some.